A retrospective study on anaemia in cats presented to the University Veterinary Hospital, Universiti Putra Malaysia from the year 2015 - Hui, Raquel Yong Li (2016)
The life-span of cat erythrocytes at approximately 73 days is shorter than that of the dog at approximately 120 days. Thus, cats are more prone to develop anaemia than dogs. In fact, anaemia is one the most common condition among cats referred to the University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM). No study has been done to characterise the type of anaemia in cats referred to UVH. Thus, the objective of this this study is to determine the classification and aetiologies of feline anaemia cases in UVH, with respect to bone marrow response. Retrospective clinical records from year 2015 were obtained and analysed. There were 162 anaemic cats, of various ages, of which 55.56% (n=90) and 44.44% (n=72)had non-regenerative and regenerative anaemia respectively. Among these cats, 65 (40.12%) were kept indoors, 59 (36.42%) were semi-roamers, and 38 (23.46%) were outdoor cats. Of vaccinated and dewormed cats, 13 (52%) cats had non-regenerative anaemia while 12 (48%) had regenerative anaemia. Among 52 cats infested with fleas,69.2% were diagnosed with hemotropic mycoplasma. Of the 52 cats, 81 % and 19 % had regenerative anaemia and non-regenerative anaemia respectively. The most common clinical signs observed in anaemic cats were dehydration, pallor, distended abdomen, and jaundice. The most common cause of anaemia in cats were infectious diseases, traumatic injury, and metabolic disorders. Sixty percent (n=18) of cats positive for either FeLV or FIV or both had non-regenerative anaemia while 40% (n=12) had regenerative anaemia. There was no significant (p>0.05) association between gender, vaccination, deworming, age, or management andthe regenerative status of anaemia. However, there wasa significant (p<0.05) positive association between flea infestation, FeLV and FIV infections and theregenerative status of anaemia in cats.